PENGGUNAAN TANAH DENGAN HAK GUNA BANGUNAN OLEH CV (TINJAUAN YURIDIS) - Dwi Sisbiantoro; Thesya Lia Nur'aini (Universitas Islam kadiri, 2022)
This research is motivated by the Circular Letter Number: 02/SE-HT.02.01/VI/2019 from the Ministry of Agrarian Affairs which provides an opportunity for CV to manage land in the form of HGB on the grounds of boosting investment. However, the contents of the letter contradict the UUPA which states that CV does not have legal rights to land management in the form of HGB. The formulation of the research problem, how is the process of obtaining HGB for CV on the basis of buying and selling and how is legal certainty and legal protection of land tenure with HGB by CV. The research objectives are to describe and analyze the process of obtaining HGB for CV, as well as to describe and analyze the legal certainty and legal protection of HGB by CV. The research method used is normative law, reviewing the Circular Letter Number:02/SE-HT.02.01/VI/2019 from the Ministry of Agrarian Affairs with the above regulations. The results of the study found that (1) The process of obtaining HGB for CV on the basis of buying and selling based on legal provisions must fulfill material and formal requirements based on statutory regulations; (2) Ownership of HGB owned by CV does not have strong legal force and has the potential to lead to lawsuits in the future.